Photoluminescence: Near‐Unity Quantum Yields from Chloride Treated CdTe Colloidal Quantum Dots (Small 13/2015). Issue 13 (April 2015) - Page, Robert C.; Espinobarro‐Velazquez, Daniel; Leontiadou, Marina A.; Smith, Charles; Lewis, Edward A.; Haigh, Sarah J.; Li, Chen; Radtke, Hanna; Pengpad, Atip; Bondino, Federica; Magnano, Elena; Pis, Igor; et al.
<x xml:space="preserve">Abstract</x> Nanocrystals of CdTe with a zinc blende structure are described by D. J. Binks and co‐workers. The surface of each is passivated by a combination of oleylamine ligands and a varying number of chloride ions, shown in the cover image as yellow spheres, that result from the treatment described on page 1548, and which results in near‐unity photoluminesence quantum yields. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>